Reliability of Serological Prestin Levels in Humans and its Relation to Otoacoustic Emissions, a Functional Measure of Outer Hair Cells. Issue 5 (15th September 2021) - Parker, Ashley; Parham, Kourosh; Skoe, Erika
Abstract : Objectives: Serological biomarkers, common to many areas of medicine, have the potential to inform on the health of the human body and to give early warning of risk of compromised function or illness before symptoms are experienced. Serological measurement of prestin, a motor protein uniquely produced and expressed in outer hair cells, has recently been identified as a potential biomarker to inform on the health of the cochlea. Before any test can be introduced into the clinical toolkit, the reproducibility of the measurement when repeated in the same subject must be considered. The primary objective of this study is to outline the test-retest reliability estimates and normative ranges for serological prestin in healthy young adults with normal hearing. In addition, we examine the relation between serum prestin levels and otoacoustic emissions (OAEs) to compare this OHC-specific protein to the most common measure of OHC function currently used in hearing assessments. Design: We measured prestin levels serologically from circulating blood in 34 young adults (18 to 24 years old) with clinically normal pure-tone audiometric averages at five different timepoints up to six months apart (average intervals between measurements ranged from <1 week to 7 weeks apart). To guide future studies of clinical populations, we present the standard error of the measurement, reference normative values, and multiple measures of reliability. Additionally, we measured transient evoked OAEs at the same five timepoints and used correlation coefficients to examine the relation between OAEs and prestin levels (pg/mL). Results: Serum prestin levels demonstrated good to excellent reliability between and across the five different time points, with correlation coefficients and intraclass correlations >0.8. Across sessions, the average serum prestin level was 250.20 pg/mL, with a standard error of measurement of 7.28 pg/mL. Moreover, positive correlations (generally weak to moderate) were found between prestin levels and OAE magnitudes and signal-to-noise ratios. Conclusions: Findings characterize serum prestin in healthy young adults with normal hearing and provide initial normative data that may be critical to interpreting results from individuals with sensorineural hearing loss. Our results demonstrate reliability of serum prestin levels in a sample of normal-hearing young adults across five test sessions up to 6 months apart, paving the way for testing larger samples to more accurately estimate test-retest standards for clinical protocols, including those involving serial monitoring. The positive correlations between serum prestin and OAE levels, although weak to moderate, reinforce that the source of serum prestin is likely the outer hair cells in the inner ear, but also that serum prestin and OAEs each may also index aspects of biologic function not common to the other.